Lycium barbarum L.: a potential botanical drug for preventing and treating retinal cell apoptosis - Xiong, Meng; Peng, Jun; Zhou, Shunhua; Gao, Qing; Lu, Jing; Ou, Chen; Song, Houpan; Peng, Qinghua (Frontiers in Pharmacology, 2025)
Retinal cell apoptosis is the primary pathological process in many retinal diseases, including retinitis pigmentosa and age-related macular degeneration, which can cause severe visual impairment and blindness. Lycium barbarum L., a traditional Chinese medicinal botanical drug, has a long history and extensive application in ophthalmic disease prevention and treatment. This study systematically reviewed the key active metabolites in L. barbarum L., including L. barbarum polysaccharides, carotenoids, and flavonoids, that exert retinal protective effects. A comprehensive analysis of the pharmacological effects and underlying molecular mechanisms of L. barbarum L. and its active metabolites in the prevention and treatment of retinal cell apoptosis, including essential aspects such as antioxidant activity, anti-inflammatory properties, autophagy regulation, and mitochondrial function preservation, is essential to establish a comprehensive and solid theoretical basis for further investigation of the medicinal value of L. barbarum L. in ophthalmology and provide a reference for future research directions.